Discovery and Development of an Advanced Lead for the Treatment of African Trypanosomiasis. - Ilbeigi, Kayhan; Dorien Mabille; An Matheeussen; Rik Hendrickx; Mathieu Claes; Nick Van Reet; Anthonissen, Roel; Fabian Hulpia; Cai Lin; Louis Maes; Clement Regnault; Phillip Whitfield; et al. (ACS Infect Dis, 2025)
African trypanosomiasis is a widespread disease of human and veterinary importance caused by various with a globally devastating impact and a need for novel treatment options. We here provide a comprehensive preclinical evaluation of nucleoside analogues, 6-thioether-modified tubercidins, with curative activity against African trypanosomiasis. Promising hits were identified following screening against the most relevant trypanosome species. Selected hit compounds were extensively tested for metabolic stability, potency in mouse models for the various species, genotoxicity in an testing battery, and mode of action studies (i.e., genome-wide RNA interference library screening and metabolomics). Among the nucleoside analogues, analogue was curative in mouse models with no indication of genotoxicity and a low ecotoxicological footprint. Mode-of-action studies revealed that P1-type nucleoside transporters and adenosine kinase are involved in the uptake and activation, respectively. Analogue represents a potent, advanced lead fitting the preferred target product profile for a broad-spectrum trypanocide regardless of the causative species.
Keywords: Animals; Disease Models, Animal; Drug Discovery; Drug Evaluation, Preclinical; Humans; mice; Nucleosides; Trypanocidal Agents; Trypanosoma; Trypanosomiasis, African; Tubercidin